A novel in vitro exposure technique for toxicity testing of selected volatile organic compounds - Khalil, C. (2006)
Exposure to vapours of volatile chemicals is a major occupational and environmental health concern. Toxicity testing of volatile organic compounds (VOCs) has always faced significant technological problems due to their high volatility and/or low solubility. The aim of this study was to develop a practical and reproducible in vitro exposure technique for toxicity testing of VOCs. Standard test atmospheres of xylene and toluene were generated in glass chambers using a static method. Human cells including: A549-lung derived cell lines, HepG2-liver derived cell lines and skin fibroblasts, were grown in porous membranes and exposed to various airborne concentrations of selected VOCs directly at the air/liquid interface for 1 h at 37 °C. Cytotoxicity of test chemicals was investigated using the MTS (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium) and NRU (neutral red uptake) assays following 24 h incubation. Airborne IC50 (50% inhibitory concentration) values were determined using dose response curves for xylene (IC50 = 5350 ± 328 ppm, NRU; IC50 = 5750 ± 433 ppm, MTS in skin fibroblast) and toluene (IC50 = 10[thin space (1/6-em)]500 ± 527 ppm, NRU; IC50 = 11[thin space (1/6-em)]200 ± 1044 ppm, MTS in skin fibroblast). Our findings suggest that static direct exposure at the air/liquid interface is a practical and reproducible technique for toxicity testing of VOCs. Further, this technique can be used for inhalational and dermal toxicity studies of volatile chemicals in vitro as the exposure pattern in vivo is closely simulated by this method.